Osoby z niepełnosprawnością na wsi – bariery integracji społecznej - Marciniak-Madejska, Natalia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The main argument of the article is the statement that the barriers of social activity and professional work for people with disabilities pile up when she or he lives in the countryside – in rural areas can be observed the accumulation phenomena impact on social marginalization. This article aims to analyze the socio-economic, communications, institutional, environmental and social obstacles that limit social participation of people with disabilities. Negative and marginalizing characteristics of the rural environment is first and foremost a low economic level, architectural barriers and difficulties in access to educational infrastructure, social and cultural data communications. The effect of this are unrealized rules of normalization of people with disabilities living in a village in areas such as education, work and leisure activities. Disparities between urban and rural areas in this field decides with fewer opportunities of development and social integration of disabled villagers.